The impact of work on cognition and physical disability: Evidence from English women - James Banks; Jonathan Cribb; Carl Emmerson; David Sturrock (Institute for Fiscal Studies (IFS), 2019)
Delaying retirement has significant positive effects on the average cognition and physical mobility of women in England, at least in the short run. Exploiting the increase in employment of 60-63 year old women resulting from the increase in the female State Pension Age, we show that working substantially boosts performance on two cognitive tests, particularly for singles. We also find large improvements in measures of physical disability as a result of working: substantial increases in walking speed, and lower reports of mobility problems. However, for women in sedentary occupations, work reduces walking speed, due to lower levels of exercise.
Keywords: 330